Analisis Motivasi Kerja, Fasilitas Terhadap Gaya Kepemimpinan dan Dampaknya pada Kualitas Jasa Layanan Perpustakaan Politeknik Negeri dan Swasta di Kota Palembang - M. Thoyib; Sopiyan AR; Periansya . (EKSISTANSI, 2013)
The quality of human resources is the key word in the face of today's global marketplace. Changes in the level of quality of human resources is often a issue in almost all organizations. Where the service quality can be affected by factors of work motivation, facilities such as reference books, information and leadership style in the university environment, especially in service in the library. This study aims to identify and analyze how far the direct influence of the three variables; motivation (X1), facilities (X2), leadership style (Y) with quality of services (Z). Sample as many as 153 respondents of 175 questionnaires were distributed from the student population of public and private polytechnics and engineering fields Busnis (not polytechnic health) in Palembang. The analysis model used is the SEM (structural equation model). Results of studies with variable conclusions berpengarh facilities directly and domnan to variable leadership style (0.49), while the third variable of motivation, facilities and leadership styles and dominant direct effect on the quality services is variable motivation (0.38).